Elaboración de hamburguesa de paco (Piaractus brachypomus) con adición de cloruro de calcio y cloruro de potasio - Saavedra Langer, Alicia Rafaela (2022)
Excessive sodium consumption brings with it negative health effects such as cardiovascular problems and hypertension, which is why the food industry sees the replacement of sodium with other types of salts as an alternative. This study aimed to reduce the content of sodium chloride (NaCl) and partially replace sodium chloride by calcium chloride (CaCl2) and potassium chloride (KCl) salts in Paco (Piaractus brachypomus) hamburger. Five treatments with different concentrations of sodium chloride (0.5%, 0.75%, 1.0%, 1.25% and 1.5%) were studied, they were partial substitutions of sodium salts by calcium salts (0.25% and 50.00%) and potassium (0.25 % and 50.00%). The centesimal content of the hamburger reported 54.00% water, 17.00% protein and 18.00% fat. The quality of the hamburger was evaluated through microbiological analysis, texture profile and shelf life through the generation of secondary oxidation products (TBARS); Likewise, the physicochemical characteristics were determined. Sensory evaluations determined a 50% (0.75%) reduction in sodium chloride content in hamburgers (1.50%). The content of sodium chloride (0.375%) was partially replaced by calcium chloride (0.375%). These results show the reduction and partial replacement of sodium chloride by calcium chloride without drastically modifying the flavor profile. Low levels of oxidation were shown for the hamburgers with the lowest salt concentrations, regardless of the type of salt.